2022
DOI: 10.1021/acs.iecr.2c02929
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Production of Glyceric Acid from Biomass-Based Sugar via the Cooperative Roles of MgO and NaBF4

Abstract: Seeking new chemo-catalytic routes to produce glyceric acid using renewable biomass-based sugar as feedstock is of significance but remains a big challenge due to a quite low yield (<5%). Herein, we prepare an MgO catalyst with an oxygen vacancy and explore a simple but robust MgO–NaBF4 system, achieving the selective production of glyceric acid from fructose with a high yield of 78.8% in an O2 atmosphere via chemo-catalysis at mild conditions (373 K), eliminating the use of strong inorganic alkalis and severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…O 2 ‐temperature programmed desorption (TPD) analysis (Figure S13 and Table S16) showed that Ag/γ‐Al 2 O 3 ‐H 2 gave much higher content of chemisorbed oxygen species/active surface oxygen species [30] when compared to Ag/γ‐Al 2 O 3 , while Ag/γ‐Al 2 O 3 ‐O 2 showed a lower content. Given the fact that Ag/γ‐Al 2 O 3 ‐H 2 had the highest Ag 0 /Ag + ratio, it was proposed that Ag 0 species in Ag/γ‐Al 2 O 3 catalyst contributed to adsorb and activate O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…O 2 ‐temperature programmed desorption (TPD) analysis (Figure S13 and Table S16) showed that Ag/γ‐Al 2 O 3 ‐H 2 gave much higher content of chemisorbed oxygen species/active surface oxygen species [30] when compared to Ag/γ‐Al 2 O 3 , while Ag/γ‐Al 2 O 3 ‐O 2 showed a lower content. Given the fact that Ag/γ‐Al 2 O 3 ‐H 2 had the highest Ag 0 /Ag + ratio, it was proposed that Ag 0 species in Ag/γ‐Al 2 O 3 catalyst contributed to adsorb and activate O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, constructing stable cathode electrolyte interface (CEI) films on cathodes and SEI layers on anodes is the key to promoting the application of etherbased electrolytes in full cells with high-potential cathodes. NaBF 4 is another commonly used sodium salt, which is also widely used in the fields of chemistry, 24,25 biotechnology, 26 pharmaceutical industry, 27 and so forth. Compared with NaPF 6 , NaBF 4 has a lower cost and shows outstanding performance when applied to ether-based electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…NaBF 4 is another commonly used sodium salt, which is also widely used in the fields of chemistry, , biotechnology, pharmaceutical industry, and so forth. Compared with NaPF 6 , NaBF 4 has a lower cost and shows outstanding performance when applied to ether-based electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…With the help of substantial NaOH (6 times), 23.5 and 25.0% yields of glyceric acid were obtained from glucose and fructose feedstock, respectively . Our group recently developed a MgO–NaBF 4 catalytic system, affording 39.4% yield (based on the total carbon in fructose) of glyceric acid from fructose feedstock . With respect to glycolic acid production from biomass, two advanced studies were reported by Han and Guan, and a <50% yield was obtained with the necessity of heteropolyacid with strong acidity.…”
Section: Introductionmentioning
confidence: 99%